2019
DOI: 10.1371/journal.pbio.3000202
|View full text |Cite
|
Sign up to set email alerts
|

PlotsOfData—A web app for visualizing data together with their summaries

Abstract: Reporting of the actual data in graphs and plots increases transparency and enables independent evaluation. On the other hand, data summaries are often used in graphs because they aid interpretation. To democratize state-of-the-art data visualization of raw data with a selection of statistical summaries, a freely available, open-source web app was written using R/shiny that uses the ggplot2 package for generating plots. Users can to choose how to display the data and which of the data summaries to add. In addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
283
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 510 publications
(283 citation statements)
references
References 18 publications
0
283
0
Order By: Relevance
“…We recommend the use of PlotsOfData (Postma & Goedhart, ) to measure statistical parameters such as mean, standard deviation, median, and 95% confidence intervals. We found that for measuring the microtubule growth and shrinkage speeds, about 20 to 50 trajectories were enough to find an accurate value, i.e., the standard deviation of speeds could not be further minimized by adding more trajectories.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…We recommend the use of PlotsOfData (Postma & Goedhart, ) to measure statistical parameters such as mean, standard deviation, median, and 95% confidence intervals. We found that for measuring the microtubule growth and shrinkage speeds, about 20 to 50 trajectories were enough to find an accurate value, i.e., the standard deviation of speeds could not be further minimized by adding more trajectories.…”
Section: Commentarymentioning
confidence: 99%
“…6. The data can now be analyzed using standard spreadsheet programs or online tools, such as PlotsOfData (Postma & Goedhart, 2019). Typical growth and shrink speeds in Arabidopsis hypocotyls lie in the range of several dozens of nanometers per second.…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…For static conditions, dotplots are a good way to graphically depict the data. Several online data visualization tools have been reported that include the option to display the actual data (Weissgerber et al, 2017;Postma and Goedhart, 2019;Goedhart, 2019;Ho et al, 2019). However, similar online tools for the visualization of continuous data seem (to the best of our knowledge) to be lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a data visualization tool for time-series data would be freely available, open source and generate high quality graphs that are publication ready. Having previously reported such a webtool for static data (Postma and Goedhart, 2019) and given the enthusiastic response by the community, we were motivated to generate a webtool for time-series data. The new web-tool that we generated is dubbed PlotTwist, for plotting data from Time-lapse experiments With Indicators of conditions at Set Times.…”
Section: Introductionmentioning
confidence: 99%